1958
DOI: 10.1002/jcp.1030520105
|View full text |Cite
|
Sign up to set email alerts
|

The pressure, temperature and ion relations of myosin atp‐ase

Abstract: The kinetics of the hydrolysis of adenosine triphosphate (ATP) by the muscle protein myosin have received considerable attention in recent years, and several reviews have been devoted to this subject (Szent-Gyiirgyi, '55; Morales et al., '55; Buchthal et al., '56). The BTP-ase activity of myosin is modified by pressure (Laidler and Beardell, '55)' by calcium, magnesium and nucleotides (Blum, '55), and by calcium, pH and temperature (Green and Mommaerts, '54; Ouellet et al., '52). The effects of pressure, tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0
1

Year Published

1958
1958
2009
2009

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
3
3
0
1
Order By: Relevance
“…9000 cal/mole. This latter value is very similar to that reported for precipitated myosin from rabbit psoas muscle at comparable temperatures (Brown et al, 1958).…”
Section: Myosin Atp-asesupporting
confidence: 90%
“…9000 cal/mole. This latter value is very similar to that reported for precipitated myosin from rabbit psoas muscle at comparable temperatures (Brown et al, 1958).…”
Section: Myosin Atp-asesupporting
confidence: 90%
“…Early investigations into the effects of high pressure on animal muscle were conducted by Cattell and Edwards (1928) and Brown (1934) who found that high pressure applied to the muscle at the onset of contraction increased the twitch tension (Cattell and Edwards 1928) while decreased rates of contraction and relaxation (Brown 1934). Both Brown et al (1958) and Ikkai and Ooi (1969) found that raised muscle hydrostatic pressure decreased the attraction of actin to myosin, thereby hindering the actomyosin ATPase reaction. Geeves and Ranatunga (1987) reported a 15% decrease in isometric active tension in a maximally calcium activated rabbit psoas muscle fiber under high hydrostatic pressures.…”
Section: Discussionmentioning
confidence: 97%
“…The effect changes on substitution of Verona1 for Tris buffer or on addition of millimolar concentrations of calcium salts. This finding is shown to reconcile the varied reports of pressure effects on myosin ATPases found in the literature (1,5,6). Although pressure also favors polymerization of myosin (7) and alters several properties of fresh and glycerinated muscle (reviewed by Brown (S)), it is premature to relate these effects to the enzymes.…”
mentioning
confidence: 56%